Type of Coronary Artery Plaque in Relation to Epicardial Fat Volume in Coronary Heart Disease Patients: A Cardiac Computed Tomography Scan Study - Iman Imaduddin Robandi; Ristaniah D. Soetikno; Dian Komala Dewi (Althea Medical Journal, 2020)
Background: Coronary heart disease (CHD) is a disease that raises public health concerns due to its high morbidity and mortality rates. Anatomically, epicardial fat is located around the heart and coronary system, making it important in the development of coronary atherosclerosis. This study aimed to explore the relationship between epicardial fat volume (EFV) and the type of coronary artery plaque by using Cardiac Computed Tomoghraphy (CT)-Scan.Methods: This was a cross-sectional observational analytic study on patients diagnosed with CHD aged > 20 years who had undergone cardiac CT-Scan at the Department of Radiology, Dr. Hasan Sadikin General Hospital, Bandung, Indonesia between February and June 2019. Data collected from the CT-Scan were analyzed using the Chi-square test.Results: From 54 CHD patients, consisting of an equal number of male and female patients, with a majority of above 60 years old (31.5%), a correlation was identified between increased amount of EFV and mix and hard plaques in the right cirumflex artery (RCA) (p<0.026) and left circumflex (LCX) (p<0.038)On the left main(LM) and left anterior descending (LAD) arteries, no significant correlation was observed between EFV and the type of plaque (p>0.05).Conclusions: There is a significant relationship between the EFV value, EFV category, and the type of coronary artery plaque in CHD patients in RCA and LCX arteries. However, this correlation is not observed in LM and LAD arteries.